Land policy and the youth bulge’ in Ethiopia: How social and economic transformations are scrutinizing the status quo - Ghebru, Hosaena (2019)
This study examines the effect of land access on youth migration and employment decisions in Ethiopia using data from Living Standard Measurement Study (LSMS)- Ethiopian Socio-economic Survey (ESS) of 2013/14 and 2015/16. An econometrics analysis is done using ordinary least square and household fixed effect estimation methods. The findings show that youth land access negatively and significantly affects permanent migration and long-distance migration. Regarding employment, land access has a significant positive and negative effect on youth agricultural employment and nonagricultural employment, respectively. The effect of land access on migration differ across various individual and community level factors. Thus, a negative and significant effect of land access on permanent migration is observed among older youth (24-35 years old) and illiterate youth. Moreover, land access negatively and significantly determines permanent migration for the youth who resides in areas with relatively higher level of agricultural modernization. Similarly, land access negatively affects youth permanent and long-distance migration in areas with relatively higher level of urbanization.